Bridging the great divide: Conspiracy theory research for the 21st century. (November 2015) - Butter, Michael; Knight, Peter
This article starts from the observation that research on conspiracy theories is currently thriving, but that it is also fragmented. In particular there is an increasing divide between disciplines with culturalist and qualitative approaches, such as history, cultural studies and ethnology, and disciplines with quantitative and empirical approaches, such as psychology and political science. The article argues that this 'great divide' has to be bridged for research to arrive at a genuine understanding of conspiracy theories. As a first step in such a bridge-building process, the article engages, from the vantage point of (American) cultural studies, with research done on the other side of the divide, namely in psychology and political science. It summarizes the work done in these fields and evaluates it critically, concentrating on methodology; the assumptions about the dysfunctionality of conspiracy beliefs; the circularity of some arguments; the focus on individual rather than social and collective aspects; the lack of engagement with the definition of the phenomenon; and the neglect of cultural and historical difference. The article ends with recommendations for future collaborative research projects.